Bạn chưa đăng nhập. Vui lòng đăng nhập để hỏi bài
Linh nguyễn

x(x+3)= (2x-1)(x+3)

Giải ptrình

Nguyễn Lê Phước Thịnh
27 tháng 2 2022 lúc 21:25

\(\Leftrightarrow\left(2x-1\right)\left(x+3\right)-x\left(x+3\right)=0\)

=>(x+3)(x-1)=0

=>x=-3 hoặc x=1

YangSu
27 tháng 2 2022 lúc 21:31

\(\text{x(x+3)= (2x-1)(x+3)}\)

\(\Leftrightarrow x^2+3x=2x^2+6x-x-3\)

\(\Leftrightarrow x^2+3x-2x^2-6x+x+3=0\)

\(\Leftrightarrow-x^2-2x+3=0\)

\(a=-1\)

\(b=-2\)

\(c=3\)

\(\Delta=b^2-4ac=\left(-2\right)^2-4.\left(-1\right).3=-3< 0\)

Vậy \(S=\varnothing\)


Các câu hỏi tương tự
Linh nguyễn
Xem chi tiết
tu duong
Xem chi tiết
Linh nguyễn
Xem chi tiết
Linh nguyễn
Xem chi tiết
Linh nguyễn
Xem chi tiết
Linh nguyễn
Xem chi tiết
Linh nguyễn
Xem chi tiết
Linh nguyễn
Xem chi tiết
Linh nguyễn
Xem chi tiết